2006
DOI: 10.1002/app.23373
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an alginate–poly(sodium acrylate‐co‐acrylamide) superabsorbent hydrogel with low salt sensitivity and high pH sensitivity

Abstract: This article describes the synthesis and swelling behavior of a superabsorbing hydrogel based on sodium alginate (NaAlg) and polyacrylonitrile (PAN). The physical mixture of NaAlg and PAN was hydrolyzed with a solution of NaOH to yield an alginate-poly(sodium acrylate-co-acrylamide) [Alg-poly(NaAA-co-AAm)] superabsorbent hydrogel. A proposed mechanism for hydrogel formation was suggested, and the structure of the product was established with Fourier transform infrared spectroscopy. The effects of reaction vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…NaAlg, a natural ionic hydrophilic linear polysaccharide containing β‐ d ‐mannuronic acid and α‐ l ‐guluronic acid (Scheme ) with OH and COO − groups are commonly used in the synthesis of hydrogels for different applications with improved mechanical properties . The sugar residues in NaAlg can either be arranged in blocks or they can be randomly distributed . Moreover, NaAlg‐based semi‐IPN was shown to be an excellent adsorbent for the removal of colored materials and toxic heavy metal ions from industrial effluent .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…NaAlg, a natural ionic hydrophilic linear polysaccharide containing β‐ d ‐mannuronic acid and α‐ l ‐guluronic acid (Scheme ) with OH and COO − groups are commonly used in the synthesis of hydrogels for different applications with improved mechanical properties . The sugar residues in NaAlg can either be arranged in blocks or they can be randomly distributed . Moreover, NaAlg‐based semi‐IPN was shown to be an excellent adsorbent for the removal of colored materials and toxic heavy metal ions from industrial effluent .…”
Section: Introductionmentioning
confidence: 99%
“…The sugar residues in NaAlg can either be arranged in blocks or they can be randomly distributed . Moreover, NaAlg‐based semi‐IPN was shown to be an excellent adsorbent for the removal of colored materials and toxic heavy metal ions from industrial effluent . Hence, semi‐IPN is viewed as one of the potential adsorbent for recycling of colored materials .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there exist only a few reports on the investigation of SAPs incorporated with clay and polysaccharides to improve their dye adsorption properties . It was reported that the organic modification of clay could improve the performance of SAPs/clay composites . Inspired by this, we prepared SAPs/clay composites using polysaccharides modified clay, the reaction was carried out under normal atmospheric conditions which caused brevity and simplicity in industrial processes …”
Section: Introductionmentioning
confidence: 99%
“…The pH-sensitive swelling characteristics of graft copolymer render it suitable for use to control drug release as a function of pH. Alginate-poly(sodium acrylate-co-acrylamide) [134] Hydrogel exhibits swelling-deswelling pulsatile behaviour at pH 2 and 8. The swelling of hydrogel decreases with an increase in ionic strength of the surrounding medium.…”
Section: Graft Copolymer Physicochemical and Drug Release Propertiesmentioning
confidence: 99%